Carbohydrate mouth rinse enhances time to exhaustion during treadmill exercise. (24th August 2015) - Fraga, Cindy; Velasques, Bruna; Koch, Alexander J.; Machado, Marco; Paulucio, Dailson; Ribeiro, Pedro; Pompeu, Fernando Augusto Monteiro Saboia
Summary: Mouth rinsing with a CHO solution has been suggested to improve short (<1 h) endurance performance through central effect. We examined the effects of mouth rinsing with a CHO solution on running time to exhaustion on a treadmill. Six well‐trained subjects ran to exhaustion at 85% VO2max, on three separate occasions. Subjects received either an 8% CHO solution or a placebo (PLA) every 15 min to mouth rinse (MR) or a 6% CHO solution to ingest (ING). Treatments were assigned in a randomized, counterbalanced fashion, with the mouth‐rinsing treatments double‐blinded. Blood samples were taken to assess glucose (Glu) and lactate (Lac), as well as the perceived exertion (RPE). Gas exchange and heart rate (HR) were collected during all trials. Subjects ran longer ( P = 0·038) in both the MR (2583 ± 686 s) and ING (2625 ± 804 s) trials, compared to PLA (1935 ± 809 s), covering a greater distance (MR 9685 ± 3511·62 m; ING 9855 ± 4118·62; PLA 7295 ± 3727 m). RER was significantly higher in both ING and MR versus PLA. No difference among trials was observed for other metabolic or cardiovascular variables (VO2, Lac, Glu, HR), nor for RPE. Endurance capacity, based on time to exhaustion on a treadmill, was improved when either mouth rinsing or ingesting a CHO solution, compared to PLA.